Interferências na sinalização adenosinérgica durante a embriogênese acarretam em alterações duradouras na morfologia e na sensibilidade a pró-convulsivantes em peixe-zebra (Danio rerio) - Menezes, Fabiano Peres (2018)
Epilepsy is the most serious neurological condition in the world. It is characterized by recurrent seizures from synchronous neuronal discharges. Disturbances in neuronal signaling in the early stages of development may lead to increased susceptibility to seizures in adulthood, as well as seizures in the early stages of development may lead to alterations in neurotransmission systems. Adenosinergic signaling is known to act as an endogenous anticonvulsant through its neuromodulatory function. Disturbances in adenosinergic signaling in early stages of development lead to changes in the susceptibility to seizures conditionally at the stage of development in which the disturbance occurs, and time of exposure to the disturbing agent. In the four chapters of this thesis, it was discussed about factors that influence the susceptibility to pentylenetetrazole (PTZ)-induced seizure under different aspects using zebrafish. In the first chapter, it was analyzed the influence of temperature on zebrafish sensitivity to PTZ as well as the ability of the MK-801 antagonist to reverse the effects of hyperthermia on susceptibility to PTZ-induced seizures. In addition, it was verifyed possible differences in the susceptibility to seizures according to gender or weight. In the second chapter, it was used transient molecular blockade through the morpholine technique to block the translation of the transcripts corresponding to the adenosinergic A1 and A2A receptors at the beginning of embryogenesis. The animals that underwent transient blockade were evaluated for survival rate and morphology, at 7 days post-fertilization (dpf) and locomotor activity and susceptibility to seizures caused by PTZ at 7 dpf and in adulthood. In the third chapter, it was used the morpholine technique to block the translation of the transcripts corresponding to the enzyme ecto-5'-nucleotidase and concentrative nucleoside transporters type 2 (CNT2) at the beginning of embryogenesis. The animals that underwent transient blockade were evaluated for survival rate and morphology at 7 days post-fertilization (dpf) and locomotor activity and susceptibility to seizures caused by PTZ at 7 dpf and in adulthood. In the fourth chapter, it was performed microinjection of the 8-Cyclopentyl-1,3-dipropylxanthine (DPCPX), antagonist of A1 receptor; ZM241385, A2A antagonist; caffeine, non-selective adenosine receptor antagonist; dipyridamole, equilibrative nucleoside transporter blocker (ENT) and Adenosine 5 '- (α, β-methylene) diphosphate (AMPCP), ecto-5'-nucleotidase enzyme inhibitor, in zebrafish eggs (1 hour post -fertilization). The animals exposed to these drugs were evaluated for survival rate, morphology and locomotor activity at 7 dpf and susceptibility to seizures caused by PTZ at 7 dpf and in adulthood. These results indicated that hyperthermia increases the susceptibility of zebrafish to PTZ-induced seizures and that this effect is prevented by the administration of MK-801. In addition, there was no difference in susceptibility to PTZ dependent on gender or body mass. These results indicated that disturbances in adenosinergic signaling through blockade via morpholine or in the higher doses of the drugs mentioned above, caused a decrease in the survival rate and high rates of morphological changes. None of the approaches caused alterations in the locomotor activity in the initial phase of development, whereas in the adult phase, there were occasional changes. At 7dpf, none of the targets blocked by morpholine caused alterations in the susceptibility to seizures caused by PTZ, whereas among the targets blocked by drugs there was alteration mainly in animals microinjected with DPCPX, Caffeine and Dipyridamole. However, in the adult phase all the targets blocked by morpholine triggered in greater susceptibility to seizures, while those blocked by drugs showed changes in specific doses and seizure stage. These results corroborate a series of studies that report the importance of adenosinergic signaling in the early stages of development as well as the deleterious effects of both exogenous and endogenous perturbations in this signaling pathway.